(untitled) (Journal of Economic Research & Business Administration, 2016)
Now the situation is such that the information contained in the statuto ry package of reporting is clearly insufficient for making justified manage ment decisions by the institution management and control over its activi ties. The information on the processes taking place in the institution in the intervals between reporting dates, separately for each section, is required for making management decisions. Therefore, the budget institutions in the new economic conditions need a management accounting, capable of forming information base for taking management decisions. The article proposes the accounting department structure in the tertia ry vocational institution during introduction of integrated system of budget and management accounting. The necessity of management accounting in tertiary educational institutions as the primary information base for taking management decisions is justified.